Eternal sentences - McGriff, Michael, 1976- (University of Arkansas Press, 2021)
"Eternal Sentences, winner of the 2021 Miller Williams Poetry Prize, bears witness to the unseen worlds of gravel roads, working-class families, and geographic isolation"--